Clickable SBA‐15 to Screen Functional Groups for Adsorption of Antibiotics. Issue 3 (21st November 2013) - Gao, Jinsuo; Zhang, Xueying; Xu, Shutao; Liu, Jian; Tan, Feng; Li, Xinyong; Qu, Zhenping; Zhang, Yaobin; Quan, Xie
Abstract Pharmaceutical antibiotics, as emerging contaminants, are usually composed of several functional groups that endow them with the ability to interact with adsorbents through different interactions. This makes the preparation of adsorbents tedious and time‐consuming to screen appropriate functionalized materials. Herein, we describe the synthesis of clickable SBA‐15 and demonstrate its feasibility as a screening material for the adsorption of antibiotics based on similar adsorption trends on materials with similar functional groups obtained by a click reaction and cocondensation/grafting methods.